Reward and Punishment Sensitivity are Associated with Cross-disorder Traits. (April 2021) - Portengen, Christel M.; Sprooten, Emma; Zwiers, Marcel P.; Hoekstra, Pieter J.; Dietrich, Andrea; Holz, Nathalie E.; Aggensteiner, Pascal M.; Banaschewski, Tobias; Schulze, Ulrike M.E.; Saam, Melanie C.; Craig, Michael C.; Sethi, Arjun; et al.
Abstract: Reversal learning deficits following reward and punishment processing are observed across disruptive behaviors (DB) and attention-deficit/hyperactivity disorder (ADHD), and have been associated with callous-unemotional (CU) traits. However, it remains unknown to what extent these altered reinforcement sensitivities are linked to the co-occurrence of oppositional traits, ADHD symptoms, and CU traits. Reward and punishment sensitivity and perseverative behavior were therefore derived from a probabilistic reversal learning task to investigate reinforcement sensitivity in participants with DB ( n =183, ODD=62, CD=10, combined=57, age-range 8-18), ADHD ( n =144, age-range 11-28), and controls ( n =191, age-range 8-26). The SNAP-IV and Conners rating scales were used to assess oppositional and ADHD traits. The Inventory of CU traits was used to assess CU traits. Decreased reward sensitivity was associated with ADHD symptom severity ( p =0.018) if corrected for oppositional symptoms. ADHD symptomatology interacted with oppositional behavior on perseveration ( p =0.019), with the former aggravating the effect of oppositional behavior on perseveration and vice versa. Within a pooled sample, reversal learning alterations were associated with the severity of ADHD symptoms, underpinned by hyposensitivity to reward and increased perseveration. These results show ADHD traits, as opposed to oppositional behavior and CU traits, is associated with decreased reward-based learning in adolescents and adults.